PERSEPSI, SIKAP DAN PERILAKU PARA GURU DI BALI TERHADAP KONSERVASI SATWA LIAR - Sang Putu Kaler Surata (Environmental Research Center (PPLH) of Udayana University)
This paper describes how the attitude and behavior of Balinese teachers toward thenatural world and its conservation, mainly wild animal. For this purpose, we conductedsurvey using a combination of open and closed-ended questions of high and middle schoolteachers at eight regency/city in Bali. There were three main topics in this survey, i.e. attitudetoward wild animal, attitude about management of wild animal and behavior toward wildanimal. The results was indicated that Balinese teacher appreciation toward wild animalvery high in natural-aesthetic, habitat-ecologistic, and consumption but lacking scientisticperspective. Concerning of wildlife conservation, we found a majority of the teacherssupported development projects if relatively significant human benefits were provided, andregardless of its impact on the rarely or endangered animals. The behavior of more thanone-half Balinese teachers showed strong affection for particularly favored wild animal,especially various species of birds. On the other hand, around three-fourth of the teachersdid not participate in activity of environmental conservation since last two years.